Women’s Alcohol Sensitivity Predicts Alcohol-Related Regretted Sex - Hone, Liana S. E. (Alcohol Clin Exp Res, 2017)
BACKGROUND: Low sensitivity (LS) to alcohol’s acute effects is a known risk factor for heavy drinking and its negative consequences. However, LS could be protective due to LS drinkers being less impaired at a given level of consumption. Here, we tested whether LS is associated with differences in men’s and women’s reports of alcohol-related regretted sex. METHODS: Eight hundred-one young adults (393 women) aged 21–35 (M = 23.11 years) recruited for a study of alcohol’s effects on cognition completed self-report measures of alcohol sensitivity, typical alcohol use, and alcohol consequences (including regretted sex). RESULTS: Participants whose alcohol sensitivity scores classified them as LS were more likely to experience alcohol-related regretted sex than were high-sensitivity (HS) participants. However, when controlling for typical alcohol use and experience of alcohol consequences in general, alcohol sensitivity was negatively associated with risk of alcohol-related regretted sex, but only among women. CONCLUSIONS: At a given level of consumption, and controlling for experience of alcohol consequences other than regretted sex, reduced sensitivity to certain effects of alcohol may be a protective factor for women against risk for alcohol-related regretted sexual situations. This study provides insight on the unique risks of drinking among LS and HS women.